Pengaruh Board Gender Diversity, Board Independence, Ceo Duality, dan Ceo Tenure Terhadap Nilai Perusahaan Perbankan yang Terdaftar di BEI pada Masa Sebelum dan Sesudah Pandemi Covid-19 - Fuadi Rachman; Gatot Nazir Ahmad; Destria Kurnianti (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This study aims to examine the effect of Board Gender Diversity, Board Independence, CEO Duality, and CEO Tenure on the Value of Banking Sector Companies Listed on the Indonesia Stock Exchange for the period Before and After Covid-19. The independent variables in this study are Board Gender Diversity, Board Independence, CEO Duality, and CEO Tenure. The dependent variable in this study is firm value which uses two proxies, namely PBV. The number of samples in this study amounted to 39 companies with 6 years of observation so that there were 234 total observations to be analysed. The sampling technique used purposive sampling method. The research method used in this research is quantitative. Data sourced based on secondary data, namely annual reports published from each company. The analysis method used is panel data regression with Stata version 17. The results of this study indicate that the results show that Board Gender Diversity has a negative effect on firm value projected by PBV value in the period before Covid-19. Conversely, Board Gender Diversity has no effect on firm value projected by PBV value in the period during Covid-19. Board Independence has no influence on firm value in the Pre Covid-19 period. Conversely, Board Independence has a positive influence on firm value at the time of Covid-19. CEO Duality has no influence on firm value in the pre-covid period or when covid struck. CEO Tenure has a significant positive effect on firm value in the Pre Covid-19 period. Conversely, CEO Tenure has no influence on firm value during Covid-19.